2021
DOI: 10.1111/tpj.15404
|View full text |Cite
|
Sign up to set email alerts
|

Open chromatin in grapevine marks candidate CREs and with other chromatin features correlates with gene expression

Abstract: Vitis vinifera is an economically important crop and a useful model in which to study chromatin dynamics. In contrast to the small and relatively simple genome of Arabidopsis thaliana, grapevine contains a complex genome of 487 Mb that exhibits extensive colonization by transposable elements. We used Hi-C, ChIP-seq and ATAC-seq to measure how chromatin features correlate to the expression of 31 845 grapevine genes. ATAC-seq revealed the presence of more than 16 000 open chromatin regions, of which we character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 107 publications
1
8
0
Order By: Relevance
“…Although ATAC-seq technology has demonstrated its power in resolving ACRs and associated TF binding sites (Lu et al, 2019;Reynoso et al, 2019;Sijacic et al, 2018), its role in plant heterosis formation remains unclear. Consistent with previous studies in other plants (Dai et al, 2022;Schwope et al, 2021), chromatin accessibility was found to be positively correlated with gene expression in tea plants. Interestingly, the total number and length of ACRs in tea hybrids were markedly larger than those in both parents, which may confer stronger transcriptional activity of the genes in tea hybrids.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although ATAC-seq technology has demonstrated its power in resolving ACRs and associated TF binding sites (Lu et al, 2019;Reynoso et al, 2019;Sijacic et al, 2018), its role in plant heterosis formation remains unclear. Consistent with previous studies in other plants (Dai et al, 2022;Schwope et al, 2021), chromatin accessibility was found to be positively correlated with gene expression in tea plants. Interestingly, the total number and length of ACRs in tea hybrids were markedly larger than those in both parents, which may confer stronger transcriptional activity of the genes in tea hybrids.…”
Section: Discussionsupporting
confidence: 91%
“…The number of ACRs and the total sequence length of the hybrids were significantly larger than those of the parents, indicating more robust chromatin accessibility of the hybrid genomes. By comparing the ATAC-seq data of multiple plant genomes reported previously (Lu et al, 2019;Schwope et al, 2021;Zhou et al, 2021), the genome proportion of ACRs in tea plants was much lower than that of plants with smaller genomes such as Spirodela polyrhiza, Arabidopsis thaliana, Eutrema salsugineum and Vitis vinifera, but higher than that of Hordeum vulgare (Figure 4b). We further examined the distribution of ACRs in the tea plant genome and classified them as gACRs (genic ACRs in exons, introns and UTRs), pACRs (proximal ACRs within 2 kb upstream of the TSS and 2 kb downstream of the TTS) and dACRs (distal ACRs in the intergenic).…”
Section: Features Of Chromatin Accessibility In Tea Hybrids and Their...mentioning
confidence: 73%
“…This approach has high sensitivity and specificity and requires few cells. ATAC-seq has been widely applied in many plants to predict cis-acting elements and chromatin accessibility [ 16 , 17 , 18 ]. Additionally, ATAC-seq has been used to assess changes in chromatin accessibility during stress responses in different plants.…”
Section: Introductionmentioning
confidence: 99%
“…2 ). In the East Asian population, we found 7 SNPs leading to the change of amino acids and 72 SNPs localized at potential promoters of genes (defined as the 2-kb region upstream of the transcription start site) ( Schwope et al 2021 ). In Eurasian, 19 missense variants and 761 SNPs located in promoter regions were observed.…”
Section: Resultsmentioning
confidence: 99%